2021
DOI: 10.1007/s43630-021-00060-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore reduction plus reversible photobleaching: how the mKate2 “photoconversion” works

Abstract: mKate red-to-green photoconversion is a non-canonical type of phototransformation in fluorescent proteins, with a poorly understood mechanism. We have hypothesized that the daughter mKate2 protein may also be photoconvertible, and that this phenomenon would be connected with mKate(2) chromophore photoreduction. Indeed, upon the intense irradiation of the protein sample supplemented by sodium dithionite, the accumulation of green as well as blue spectral forms is enhanced. The reaction was shown to be reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…We are happy to announce that today, this virtual volume unites 18 contributions by scientists from 17 countries (Canada, Czech republic, Finland, France, Germany, Hungary, India, Italy, Japan, Lebanon, Poland, Russia, Spain, Switzerland, Taiwan, UK, US) touching upon the wide variety of the subjects dealt with by Klaus at various times [25,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
See 1 more Smart Citation
“…We are happy to announce that today, this virtual volume unites 18 contributions by scientists from 17 countries (Canada, Czech republic, Finland, France, Germany, Hungary, India, Italy, Japan, Lebanon, Poland, Russia, Spain, Switzerland, Taiwan, UK, US) touching upon the wide variety of the subjects dealt with by Klaus at various times [25,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
“…A paper from Protasova et al investigates the mechanism of colour change in mKate2, an engineered red fluorescent protein used as popular marker in cell biology [137]. The authors found that the unsual red-to-green transformation is in fact due to a pre-existing green fraction that becomes better visible upon bleaching of the red form.…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
“…A further investigation showed that the crosstalk phenomenon is universal for all the tested RFPs that survived standard EM sample preparation (Figure S8). A very likely reason is that under high-energy illumination, severe chromophore photoreduction happens that leads to obvious red-to-green photoconversion of the RPFs, a mechanism that has been reported before [2426].…”
Section: Resultsmentioning
confidence: 95%
“…A further investigation showed that the crosstalk phenomenon is universal for all the tested RFPs that survived standard EM sample preparation ( Figure S2 ). A very likely reason is that under high-energy illumination, severe chromophore photoreduction happens that leads to obvious red-to-green photoconversion of the RPFs, a mechanism that has been reported before [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 96%